LIBRARY AUTOMATION SYSTEM USING RFID (International Journal of Food and Nutritional Sciences, 2022)
Radio Frequency Identification system (RFID) is a compilation of radio frequency based technology and microchip technology that helps in library for theft detection. It is used in libraries for automation of repetitive work like issuing and returning of books. In spite of economic hardship, libraries are taking in view of new technology such as RFID for cost saving in library operation and effective management for material flows. This RFID helps in libraries in many ways such as identification of book, self check out, storage of major information etc. and also reduces the data entry errors, magnify the customers service and updation of records. This paper describes the History of RFID tags, advantage and disadvantage , records updates, implementation of RFID in Indian libraries, enhance customer service , and plays important role to make every one’s job easier right from user to library staff.